Allied Constructive Criticism? The EU and Crises In Its Immediate Neighbourhood from the American Perspective (Politeja, 2019)
The main aim of the article is to answer the question of how the involvement ofthe European Union (EU) in its immediate neighbourhood, and in particular the European Neighbourhood Policy (ENP), is perceived by American foreignpolicy experts. What aspects of EU activities are assessed positively, and which are the most controversial? Particular attention is paid to the key challenges that the EU has been facing in recent years – the Ukrainian crisis and the political consequences of the so-called Arab Spring of 2011, with a special focus on migration pressure in the Mediterranean region. The analysis focuses how EU roles are perceived by American political actors. As the most important international actor, the views of the United States regarding the EU’s activity have a significant influence on what the EU does. The study is based on interviews conducted with experts and political actors of American foreign policy in 2015 and 2016.